2018
DOI: 10.3390/brainsci8120208
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Context-Driven Reinstatement of Methamphetamine Seeking is Associated with Distinct Neuroadaptations in the Dentate Gyrus

Abstract: The present study examined differences in operant responses in adult male and female rats during distinct phases of addiction. Males and females demonstrated escalation in methamphetamine (0.05 mg/kg, i.v.) intake with females showing enhanced latency to escalate, and bingeing. Following protracted abstinence, females show reduced responses during extinction, and have greater latency to extinguish compared with males, indicating reduced craving. Females demonstrated lower context-driven reinstatement compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Both sexes are included in these studies because differences occur in metabolism 29 and acquisition of drug self-administration 30,31 , and in basic and synaptic excitatory transmission 11,32 . However, our behavioral endpoint, cued reinstatement, is not sensitive to sex as a biological variable 33,34 unless the response ratio is increased during the reinstatement test 33 .…”
Section: Methodsmentioning
confidence: 99%
“…Both sexes are included in these studies because differences occur in metabolism 29 and acquisition of drug self-administration 30,31 , and in basic and synaptic excitatory transmission 11,32 . However, our behavioral endpoint, cued reinstatement, is not sensitive to sex as a biological variable 33,34 unless the response ratio is increased during the reinstatement test 33 .…”
Section: Methodsmentioning
confidence: 99%
“…Extinction of cocaine-induced CPP took longer in male compared with female adolescent rats (110). More recent work has shown that after similar extinction training, context-induced reinstatement of methamphetamine seeking was more pronounced in male compared with female rats (381). Further, the study showed that this difference in methamphetamine seeking between male and female rats was possibly mediated by differential plasticity in the dentate gyrus in the hippocampus.…”
Section: Future Directionsmentioning
confidence: 99%
“…Dopaminergic mesocorticolimbic system has been related with motivation in drug intake and relapse in drug-seeking behaviour [ 2 , 16 ]. Of all the dopaminergic receptors, the D3 receptor (D3R) seems to be uniquely implicated in reward, motivation, emotion, learning, and, by extension, drug seeking and relapse mechanisms, given its restricted distribution in the limbic system [ 17 , 18 , 19 ]. As a member of the D2-like receptor family, D3R is coupled to the Gα i/o protein, and thus inhibits adenylyl cyclase and diminishes the intracellular levels of cAMP.…”
Section: Introductionmentioning
confidence: 99%